1895 N.D. Rev. Codes 1299, Penal Code, ch. 43, § 7358 - (:unkn) unknown (My University, 1895)
Every person who willfully discharges any species of firearm, air gun or other weapon or throws any missile in any public place or in any place where there is any person to be endangered thereby, although no injury to any person shall ensue, is guilty of a misdemeanor.]
Keywords: DISCHARGE